Doctor's presenteeism and its relationship with anxiety and depression: a cross-sectional survey study in China. Issue 7 (30th July 2019) - Xi, Xiaoyu; Lu, Qianni; Wo, Tian; Pei, Pei; Lin, Guohua; Hu, Hao; Ung, Carolina Oi Lam
Abstract : Objectives: The impact of presenteeism on doctors' health, quality of patient care and overall performance of health institutions has been reported. The study aimed to investigate the prevalence of presenteeism among doctors, the association between presenteeism and anxiety/depression, and aspects that can help alleviate presenteeism. Design: A cross-sectional anonymous survey study was conducted between 2017 and 2018. Setting: 30 hospitals in Hangzhou city, Zhejiang Province, China including 10 category 1 hospitals (20–99 beds), 10 category 2 hospitals (100–499 beds) and 10 category 3 hospitals (> 500 beds) which had the highest population coverage. Participants: At least 3 doctors from each department in the studied hospitals participated. Each participant received a gift worth around US$5 at completion of the survey. Primary and secondary outcome measures: The prevalence of presenteeism and its relationship with anxiety or depression were evaluated as the primary outcomes. Secondary outcomes included the prevalence of abnormal cases of anxiety and depression. Results: The survey was completed by 1153/1309 hospital doctors (response rate 88.1%). Presenteeism was reported by 66.4% of participants. Using the Hospital Anxiety and Depression Scale, 68.8% and 72.3% of participants had abnormal cases of anxiety and depression, respectively. Logistic regression analysis showed that participants with abnormal cases of anxiety, borderline cases of depression or abnormal cases of depression were more likely to practice presenteeism (all p<0.05). Other significant work-related contributing factors included: time working at the current hospital, management duty, monthly salary and ease of replacement (all p<0.05). Conclusion: Presenteeism was prevalent among doctors in China and the association of presenteeism with abnormal cases of anxiety or depression was significant. Considering the modifiable work-related contributing factors, appropriate measures at the healthcare institutions to support doctors' mental health, help them develop and reinforce management skills, and ensure appropriate manpower are important to alleviate presenteeism behaviour.